Fouling in refineries - Speight, James G. (Amsterdam : Elsevier : Gulf Professional Publishing, 2015)
Fouling in Refineries is an important and ongoing problem that directly affects energy efficiency resulting in increased costs, production losses, and even unit shutdown, requiring costly expenditures to clean up equipment and return capacity to positive levels. This text addresses this common challenge for the hydrocarbon processing community within each unit of the refinery. As refineries today face a greater challenge of accepting harder to process heavier crudes and the ongoing flow of the lighter shale oil feedstocks, resulting in bigger challenges to balance product stability within.
3.4.1. Dehydrogenation3.4.2. Dehydrocyclization; 3.4.3. Isomerization; 3.4.4. Alkylation; 3.4.5. Polymerization; References; Chapter 4: The Stability of Petroleum; 4.1. Introduction; 4.2. The Petroleum System; 4.3. Stability/Instability of the Petroleum System; 4.4. Effects on Recovery and Refining; 4.4.1. Recovery Operations; 4.4.2. Refining Operations; 4.5. Epilog; References; Chapter 5: Analytical Methods; 5.1. Introduction; 5.2. Standard Test Methods; 5.2.1. Elemental Analysis; 5.2.2. Density; 5.2.3. Volatility; 5.2.4. Viscosity; 5.2.5. Asphaltene Content; 5.2.6. Pour Point
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed May 19, 2015).
Elsevier
Keywords: Petroleum refineries; Fouling; TECHNOLOGY & ENGINEERING / Power Resources / General; Fouling -- History; Fouling organisms; Fouling; Fouling; Petroleum refineries; Electronic books; Electronic books